The new humanism and communication - Villarreal, Ana Lucía (2012)
This article presents some contributions to the understanding of humanism from the paradigm of complexity. Also discussed the crisis of paradigms and the emergence of new world views in the light of advancing scientific knowledge. It discusses the concept of Third Culture and communication as a human process.